Intellectual property rights - M Ashok Kumar Ed; Ali, Mohammed Iqbal Ed (New Delhi Serials Publications, 2008)
Book Summary of Intellectual Property Rights Since the establishment of WTO, the issue of protection and harmonization of Intellectual Property Rights has been gaining momentum. The developed countries have been in particular, keen for implementation of the provisions of the TRIPS Agreement
Keywords: Patents; Copyright; Copyright Protection